Menumbuhkan Urgensi pada Produk Hijau dalam Membangun Keberlanjutan Lingkungan - Sri Rahayu; Nabila Kharimah Vedy; Sudarwati Sudarwati; Evi Novita Sari Novita Sari; Etiya Toharoh (LPPM ITB AAS Indonesia Surakarta, 2023)
Economic activity creates negative externalities for the environment. In this case, the use of raw materials without proper waste management can damage the ecosystem and the environment. Public awareness to manage waste such as cooking oil can provide economic benefits and environmental damage. Departing from these problems, the solution offered is to conduct training on creating environmentally friendly products such as hand washing from cooking oil waste and conduct in-depth education with the community regarding the importance of environmental management (sustainability). This community service activity was held in the Village Labuhan Ratu II, East Lampung. Meanwhile, the activity was attended by housewives and MSME actors. This community service activity raises awareness for the community in East Lampung Village about the importance of maintaining environmental sustainability and improving skills to utilize waste into salable products. Keywords: green products, sustainability, recycle, cooked Oil, Green Marketing, Green Behaviour